Biodegradable waste-derived cellulose/nylon-6-coated iron-oxide nanocomposite encapsulated with chitosan for enhanced wastewater treatment - Evans Suter; H.L Rutto; I.G Mkhize (Cleaner Chemical Engineering, 2025)
The growing threats of water scarcity, climate change, and waste accumulation necessitate innovative solutions, including the transformation of solid waste into sustainable new materials through recycling technologies. This study prepared a low-cost, superior and biodegradable polymeric material made of cellulose nanocrystals from waste paper and pulp sludge, nylon-6 waste, magnetic iron oxide nanoparticles, and chitosan. The nanocomposite membrane presented saturation magnetization of 26.90 emu/g, significantly lower than magnetic saturation (Ms) of magnetic iron oxide nanoparticles (Fe3O4). This resulted from the addition of cellulose nanocrystals (CNCs), nylon 6 (N6), and Chitosan (CT), as confirmed by Fourier Transform Infrared (FTIR). Scanning electron microscopy (SEM) revealed that the ultra-permeable membrane had highly porous surfaces. Brunauer Emmet Teller (BET) demonstrated that the addition of chitosan and Fe3O4 boosted nitrogen adsorption. The isoelectric point (IEP) pH at zero point charge (pHPZC) of magnetized cellulose nanocrystals/nylon 6 nanocomposite membrane encapsulated with chitosan (CNCs/N6@Fe3O4CT) was 7.9 due to the hydroxyl groups on the amphoteric surface that react with bases or acids to create a pHPZC that is extremely near to neutral. The nanocomposite presented a larger swelling ratio of 168.24 g/g than precursor materials. The membrane demonstrated excellent rejection efficiency, initiating at approximately 98 %. The resulting nanocomposite membrane's remarkable water permeability, porosity, good rejection, and flux, even at low pressure, offers a potential for water treatment and air filtration applications.